The Significance of Destination Image for Freediving as a Form of Alternative Tourism in Tulamben, Bali - Lintangkawuryan, Yulia (Institut Pariwisata Trisakti, 2020)
In the last few years, freediving has been growing rapidly as a form of alternative tourism. These activities aim at hunting view, spearfishing, taking photos, witnessing the beauties of the objects like the flora, fauna, and the archaeology of underwater. This research aims to give a descriptive potential to increase freediving awareness as an alternative activity to explore the underwater flora and fauna heritage of Tulamben and bring them into tourism. The history and development of Tulamben are intimately linked to the sea. Tulamben area possesses a rich underwater cultural and natural heritage, which reflects its identity and should be protected for future generations. This new interest is becoming more famous for its underwater richness. This move also guides some to form a new underwater sports center, especially for freediving enthusiasts, to contribute to the region's potential improvement. This project also aims to improve extreme underwater sports like freediving, which is now a hobby than a sport. The research method carried out in this study is a qualitative method with a descriptive approach because this study aims to obtain a complete picture of freediving as a form of alternative tourism in Tulamben, Bali. From the result, it can be concluded that freediving could be potential alternative tourism in Tulamben for its good destination image. Keywords: Freediving, Alternative Tourism, Underwater Tourism, Tulamben